Sustainability transitions: the role of systems thinking in improving planetary health and human prosperity - Souliotis, Ioannis; Voulvoulis, Nikolaos (Frontiers in Environmental Science, 2025)
Addressing complex global environmental and socio-economic challenges requires a fundamental transition to sustainability, as current systems are inadequate to manage climate change, poverty, inequality, and resource depletion. For decades, research has linked economic development to environmental degradation, reinforcing the belief that economic growth and environmental protection are inherently in conflict. Consequently, opposing perspectives have emerged: one advocating limits to growth to safeguard the environment, and another asserting that technological progress can sufficiently substitute natural for man-made capital. Despite growing awareness of ecological decline, the absence of a compelling vision of a sustainable future, beyond dystopian scenarios of collapse or business-as-usual projections focused on incremental change, continues to delay real progress. Through a systems-thinking lens, defined here as an approach that views social, economic, and ecological phenomena as interdependent components of a single dynamic system shaped by feedback loops, nonlinear interactions, and emergent properties, we revisit the relationship between growth and environmental degradation, outline a new vision for sustainable development that recognises humans as part of nature, and explore the role of economics and policy in realising this vision. We argue that only systemic change and integrated approaches grounded in a deeper understanding of human–nature interactions can deliver the transformations needed to improve both planetary health and societal prosperity.